The pattern of neural tube defects in a highly endogamous society: A 25-year incidence trends - Bener, Abdulbari; Kurdi, Bader; Hoffmann, Georg F.; Caksen, Huseyin; Teebi, Ahmad (Journal of Pediatric Neurology, 2012)
The wide variety in incidence rates of neural tube defects (NTD) in the Arabian region have been attributed to environmental, dietary and genetic factors. No previous study has been conducted in the State of Qatar to document the incidence and trends of NTD. The aim of this study is to determine the incidence and trends of NTD over a period of 25 yr in the State of Qatar. This is a retrospective hospital based cohort study. The survey was carried out in the main territory hospital in the State of Qatar. The study was conducted from 1985 to 2009 with a total of 302,049 newborns at the Women's Hospital in Qatar screened for NTD. NTD were defined according to the International Classification of Diseases, Tenth Revision. Study parameters included age, gender, ethnicity, parental consanguinity, and residential area. The combined prevalence of NTD (total myelomeningocele and anencephaly) during the 25 yr period was 1.09 per 1,000 births. The prevalence of anencephaly was 0.36 per 1,000 births. There were 131 (42.1%) males and 180 (57.9%) female newborns with NTD, corresponding to incidence of 0.899 and 1.289 per 1,000 in male and female newborns, respectively. This difference was significant (P < 0.001). Consanguinity was seen in 36.7% of the parents. The present study revealed that Qatar has a relatively low incidence of NTD, which is comparable to neighboring countries in the Arabian Gulf region. High rates of consanguinity and lack of periconceptual folic acid intake among mothers appear to be the major factors contributing to NTD in Qatar.
Keywords: Incidence; neural tube defects; birth weight; gestational age; consanguinity; vitamin B12; folate